"How could neuroimaging be helpful in the assessment of Dementia in a clinical setting? " - Malakouti K (Acta Medica Iranica, 2002)
This study was conducted to evaluate how neuroimaging procedures (MRI, SPECT) could be used in clinical setting for diagnosis of dementia.Forty out of 94 patients suspected of having a diagnosis of dementia, referred to Radiology Department for consecutive neuroimaging procedures, were selected. Patients’ medical records reviewed anda retrospective diagnosis was reached according to DSM-IV for Alzheimer’s disease (AD) and NINDS-AINS for vascular dementia (VaD). Mann-Whitney, fisher’s exact test, bivariat regression were used for analysis.Clinical features of majority of patients were complicated with mental symptoms. Subcortical lesions were observed in both dementias but it was significantly more frequent in the VaD (P=0.000). No significant differences in the number of patients with cortical atrophy between two groups was observed. Significant agreement between SPECT and retrospective clinical diagnosis was observed (kappa=0.18, P=0.02), but no significant pattern of hypoperfusion which could predict the clinical diagnosis was observed.This study emphasis on clinical diagnosis and the clarity of the referral process for doing neuroimaging evaluation. More sophisticated studies, either structural of functional such as volumetric measurement of medial temporal lobe, could be helpful to confirm clinicians in their diagnosis of patients with dementia.